2018
DOI: 10.1002/chem.201802881
|View full text |Cite
|
Sign up to set email alerts
|

Arginine/Tryptophan‐Rich Cyclic α/β‐Antimicrobial Peptides: The Roles of Hydrogen Bonding and Hydrophobic/Hydrophilic Solvent‐Accessible Surface Areas upon Activity and Membrane Selectivity

Abstract: The bacterial selectivity of an amphiphilic library of small cyclic α/β-tetra-, α/β-penta-, and α/β-hexapeptides rich in arginine/tryptophan (Arg/Trp) residues, which contains asymmetric backbone configurations and differ in hydrophobicity and alternating d,l-amino acids, was investigated against Bacillus subtilis and Escherichia coli. The structural analyses showed that the peptides tend to form assemblies of different shapes. All-l-peptides, especially the most hydrophobic pentamers, were more strongly anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 72 publications
0
22
0
Order By: Relevance
“…[9] As a result, the majority of clinical applicable AMPs are used or designed for topical applications only with very few exceptions aimed for systematic applications. [5] To overcome these limitations, many different strategies, including but not limited to structural/ sequence modification, [10][11][12][13] specific delivery system design, [14][15][16][17] "smart" AMPs [18][19][20] and de novo designed antimicrobial peptides/peptidomimetics [21][22][23][24][25][26][27] have been developed to efficiently use AMPs without being hindered by their side-effects. Among these strategies, modification or mimicry of naturally occurring peptides with natural amino acids or unnatural building blocks is an efficient pathway.…”
Section: Introductionmentioning
confidence: 99%
“…[9] As a result, the majority of clinical applicable AMPs are used or designed for topical applications only with very few exceptions aimed for systematic applications. [5] To overcome these limitations, many different strategies, including but not limited to structural/ sequence modification, [10][11][12][13] specific delivery system design, [14][15][16][17] "smart" AMPs [18][19][20] and de novo designed antimicrobial peptides/peptidomimetics [21][22][23][24][25][26][27] have been developed to efficiently use AMPs without being hindered by their side-effects. Among these strategies, modification or mimicry of naturally occurring peptides with natural amino acids or unnatural building blocks is an efficient pathway.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the structural stability, Dathe et al (152) were able to create a series of short cyclic hexapeptides (based on AcRRWWRF-NH 2 ) with enhanced antimicrobial efficacy (up to >16-fold increase) against Bacillus subtilis and E. coli compared to the linear form, though the hemolytic activity was increased by 3-fold (152). It was also found that the antimicrobial activities of those small Arg/Trp-rich cyclic peptides were influenced by the self-assembling behavior of peptides at the bacterial membrane instead of their hydrophobic surface area, amphiphilicity, and ring size (153). In addition, a number of small cyclic D,L-alphapeptides (with six or eight alternating D-and L-form residues) have also demonstrated strong antimicrobial efficacy against Gram-positive and/or Gram-negative bacteria via self-assembly on the bacterial membranes as organic nanotubules, which could increase membrane permeability and disrupt transmembrane ion potentials with resultant cell lysis (154,155).…”
Section: Cyclizationmentioning
confidence: 99%
“…Peptide cyclization with limited conformational flexibility not only provides large surface area, which could enhance membrane-binding affinity but also prevents protease degradation. Until now, there are three common types of cross-linking construction: All-hydrocarbon stapling system [ 184 , 185 ], disulfide bonds and its modification [ [186] , [187] , [188] , [189] ] and lactam-bridge [ [190] , [191] , [192] ] ( Fig. 4 ).…”
Section: Approaches To Improve Biological Activities Of Ampsmentioning
confidence: 99%